The Effect Of Reproductive Health Education On Increasing Pre-Conception Knowledge In Young Girls At Yaspih High School Tangerang Banten In 2023 - Diah Rohayati; Maryati Sutarno (International Journal of Health and Pharmaceutical (IJHP), 2024)
Background: Reproductive and sexual health education is very necessary in achieving the growth and development tasks that must be passed by a teenager. The preconception period is the period before conception or before pregnancy occurs and the period between conceptions which can begin within two years before conception. Purpose of Writing: To determine the effect of reproductive health education on increasing pre-conception knowledge for young women. Research Methods: This type of research uses a quasy experimental design with a one group pre-test post-test design, the sample in this study is 74 people, the Wilcoxon statistical analysis test. Research results: there are differences in knowledge before and after being given reproductive health education (p value = 0.000), it can be concluded that the Effect of Reproductive Health Education on Increasing Preconception Knowledge in Young Girls at SMA Yaspih Tangerang Banten. Conclusions and Suggestions: It is hoped that the results of this study can be used as a reference for female students to increase reproductive health knowledge in future pre-conceptional health in women.